Study of Prebiotic Potency Sweet Potato Flour With Difference of Varieties as Complementary Feeding - Fitri, Imelda; Mursyida , Eliya (Institut Kesehatan dan Teknologi Al Insyirah, 2024)
Infant’s complementary feeding innovation by using the local food Ipomoea Batatas with four variants they are orange, purple, yellow and white. Purpose of the research was to determine the potency prebiotic, from four flour variants. Design of the research was experimental study with completely random design. The research was operated on June until October of 2022 at Laboratory of Abdurrab University. Steps of the research were by the flour making, and the prebiotic potency test. The data was analyzed by Huebner’s method to know the prebiotic’s activity score. The research’s outcome was existence of the bacteria amount increasing of L.parasei for the purple Ipomoea Batatas (8,54 log CFU mL-1). The purple Ipomoea Batatas contained better prebiotic potency than orange, yellow and white Ipomoea Batatas.